Prenatal diagnosis of critical congenital heart disease associated with lower postpartum depressive symptoms: a case-control study - Daniela R. Vieira; Patrícia P. Ruschel; Márcia M. Schmidt; Paulo Zielinsky (Jornal de Pediatria)
Objective: When the expectant mother is faced with an unforeseen event during pregnancy, she may experience emotional fragility and depression. This study was carried out to test the association between the time of diagnosis of critical congenital heart disease (CCHD) and depressive symptoms in puerperal women. Method: A case-control study. All mothers answered a semi-structured questionnaire and the Edinburgh Postnatal Depression Scale (EPDS). Pearson's correlation and multiple linear regression analysis were used to determine factors associated with depression. Results: 50 puerperal women, 23 cases and 27 controls. The proportion of puerperal depressive symptoms was 26.1 % among mothers of infants prenatally diagnosed with CCHD and 77.8 % among mothers of infants postnatally diagnosed (p = 0.001 [OR] 9.917; 95 % CI 2.703–36.379). Multiple linear regression analysis showed that the use of psychotropic drugs and time of diagnosis were significantly associated with puerperal depressive symptoms. Conclusion: Prenatal diagnosis of CCHD was associated with significantly lower levels of depressive symptoms.